Salbutamol Nebulization In The Treatment Of Hyperkalemia - N. KARUNA SREE; R.NARASIMHA RAO (International Journal of Pharma and Bio Sciences, 2011)
Thirty patients with hyperkalemia (serum K+ levels > 5.5 meq/l) due to severe renal failure were included in the study.10mg salbutamol was given as nebulization over 10 mts in a propped up position through face mask and patient encouraged to take deep breath. Serum potassium levels at 0,1,4 and 6 hrs, ECG before and after nebulization, Serum Glucose, Blood urea, Serum Creatinine, Pulse which were recorded in a bi- hourly basis showed a reduction in Serum K+. Also ECG showing Tall T waves were reverted to normal and conduction blocks disappeared. Thus, salbutamol nebulization is an effective tool in the emergency management of hyperkalemia with ease of administration, technical simplicity, good tolerability without significant adverse effects, quick initial correction of hyperkalemia either as initial monotherapy or in combination with other modalities as a temporary measure for transcellular shift of K+ until a definitive therapy like hemo-dialysis could be instituted.